The quality of life needs of Xhosa speaking learners with Down Syndrome : two case studies - Skota, Bekisisa Andrew (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEdPsych (Educational Psychology))--University of Stellenbosch, 2007.